How do you solve 4( - 12d - 12) = 6( 8- 6d )?

1 Answer
Jun 22, 2018

Use the distributive property, combine like terms, and divide.

Explanation:

The distributive property states that a(b+c)=a*b+a*c. Let's use this to simplify both sides:

4(-12d-12)=4*-12d+4*-12=-48d-48
6(8-6d)=6*8+6*-6d=48-36d

We now have -48d-48=48-36d. Next, let's combine like terms to isolate d on one side:

-48d-48+48=48-36d+48

-48d=-36d+96

-48d+36d=-36d+96+36d

-12d=96

Finally, let's divide each side by -12:

(-12d)/-12=96/-12
d=-8

Hope this helps!